Impact of the White Collar Photoreceptor WcoA on the Fusarium fujikuroi Transcriptome - Pardo-Medina, Javier; Gutiérrez, Gabriel; Limón, M. Carmen; Avalos, Javier (Frontiers in Microbiology, 2021)
The proteins of the White Collar 1 family (WC) constitute a major class of flavin photoreceptors, widely distributed in fungi, that work in cooperation with a WC 2 protein forming a regulatory complex. The WC complex was investigated in great detail in Neurospora crassa, a model fungus in photobiology studies, where it controls all its major photoresponses. The fungus Fusarium fujikuroi, a model system in the production of secondary metabolites, contains a single WC-1 gene called wcoA. The best-known light response in this fungus is the photoinduction of the synthesis of carotenoids, terpenoid pigments with antioxidant properties. Loss of WcoA in F. fujikuroi results in a drastic reduction in the mRNA levels of the carotenoid genes, and a diversity of morphological and metabolic changes, including alterations in the synthesis of several secondary metabolites, suggesting a complex regulatory role. To investigate the function of WcoA, the transcriptome of F. fujikuroi was analyzed in the dark and after 15-, 60- or 240-min illumination in a wild strain and in a formerly investigated wcoA insertional mutant. Using a threshold of 4-fold change in transcript levels, 298 genes were activated and 160 were repressed in the wild strain under at least one of the light exposures. Different response patterns were observed among them, with genes exhibiting either fast, intermediate and slow photoinduction, or intermediate or slow repression. All the fast and intermediate photoresponses, and most of the slow ones, were lost in the wcoA mutant. However, the wcoA mutation altered the expression of a much larger number of genes irrespective of illumination, reaching at least 16% of the annotated genes in this fungus. Such genes include many related to secondary metabolism, as well as others related to photobiology and other cellular functions, including the production of hydrophobins. As judged by the massive transcriptomic changes exhibited by the wcoA mutant in the dark, the results point to WcoA as a master regulatory protein in F. fujikuroi, in addition to a central function as the photoreceptor responsible for most of the transcriptional responses to light in this fungus.